Judith Bernays Heller papers - Heller, Judith Bernays
Correspondence, diaries, speeches, and writings pertaining to Heller's life in Europe and the U.S., her travels in Europe, Sigmund Freud, and the Freud household. Correspondents include Heller's mother, Anna Freud Bernays, and Heller's cousin, Anna Freud.
Teacher, author, and niece of Sigmund Freud. Born 1885; married Victor Heller, economist, in Vienna, Austria, 1922; died 1977.
Collection material in English, French, and German.
Forms part of: Sigmund Freud collection.
Keywords: Bernays, Anna Freud, -- 1858-1955 -- Correspondence; Freud, Anna, -- 1895-1982 -- Correspondence; Freud, Sigmund, -- 1856-1939.; Freud family; Europe -- Description and travel; Authors; Teachers